Screening and breeding for resistance to maize stem borers and Eldana in West and Central Africa - Ajala, S.; Aroga, R.; Odiyi, A.; Olaoye , G. (2009)
Stem borers are one of the major constraints limiting maize productivity in Africa. The most important species reducing maize yield in West and Central Africa are Sesamia calamistis, Eldana saccharina and Busseola fusca. Both the pink stem borer (Sesamia calamistis Walker (Pyralidae) and the sugarcane borer Eldana saccharina Hampson (Noctuidae) infest and reduce maize yields in the lowlands of West and Central Africa. Host pant resistance is very effective in managing the pests and researches conducted in the sub-region have identified promising genotypes with resistance to the two borer species. Such genotypes have been utilised to develop improved varieties with better levels of resistance. Genetic studies revealed that both additive and non-additive gene actions are important in varying degrees for the different components of resistance. The improved varieties are being strategi- cally deployed on-farm while other adapted varieties are being improved for resistance to enhance their usefulness. Progress made in screening and breeding for stem borer resistance in the region is discussed.